Od kapitalizmu informacyjnego do kapitalizmu inwigilacyjnego - Puślecki, Zdzisław W. (Humaniora. Czasopismo Internetowe, 2021)
The digital revolution imposes a new economic order. Surveillance capitalism has its origins in (classical) market capitalism, but it differs significantly from it. In the traditional (classical) model of capitalism, there are goods that are produced in order to be sold. However, in the 21st century it is difficult to compete. It is not easy to find new added value that would determine the margin and profit. The question is, how long can you keep your labor costs down? This is why surveillance capitalism arose. His story is relatively young. It was established in the years 2000–2004. As the Internet bubble burst, investors threatened the company to pull out of funding, unable to find a quick way to monetize it. Then Google suddenly discovered that the last virgin territory that had not yet hit the market was human nature. It is worth noting that it is much easier to predict something if you first interfere with the behavior so that it takes the desired forms. To put it bluntly – the market is trying to push its individual participants, as customers and consumers, more and more in the direction it prefers, trying to influence their opinions, sometimes even driving them to specific places. The aim of the study is to present the problems that led to the transformation of information capitalism into surveillance capitalism.